Moral value analysis of the film KKN di Desa Penari (Luwih Dowo Luwih Medeni) - Puji Lestari, Ayu; Kanzunnudin, Mohammad; Darmuki, Agus (Saba Jaya Publisher, 2024)
This research is motivated by the emergence of films that are inseparable from the development of technology and science so that they are able to create a great achievement in visual language in film art. The films that are made are certainly not just for entertainment, but there are messages, good things, and useful things that should be used as examples, which the scriptwriters or story writers of the film want to convey. The purpose of this study is to describe the moral values ??contained in the film KKN di Desa Penari (Luwih Dowo Luwih Medeni). This study uses a qualitative descriptive research method. The collection of research data uses data reduction techniques, data presentation, and drawing conclusions. The results of this study explain the moral values ??contained in the film KKN di Desa Penari (Luwih Dowo Luwih Dowo).